Aquaculture and its effect on the wild fish resource in a Swedish lake : An evaluation of changes in fat content, protein content and trophic niche - Nyberg, Emmy (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2022)
Fish is nutritious and important as a food source for many people. It contains high levels of protein, important omega-3 fatty acids as well as micronutrients. For a sustainable fish consumption, aquaculture is needed but it can affect nearby ecosystems in many ways. This study aimed to evaluate the effect of aquaculture on wild Arctic charr, burbot, perch and whitefish, in a lake with a newly established fish farm in northern Sweden. Fish were caught in three different locations (aquaculture, downstream, upstream) at three different occasions (year 2009, 2010, 2012). Fish caught in 2009 were sampled the first year after establishment of the aquaculture, with low impact from the farm and hence assumed to be “before” establishment, while 2012 and 2012 were assumed to be “after”. Analyses of fat- and protein content were performed in all four species of the wild fish from the different capture locations and capture years. Additionally, stable isotopes of carbon and nitrogen were analysed in perch and whitefish from different capture years and capture locations. Fat content increased over time in burbot and whitefish whereas it both decreased and increased in perch, depending on capture location. Protein content did not change significantly over time in any of the species. Charr was not statistically evaluated due to low sample size. The stable isotope analysis indicated some changes after establishment of the aquaculture. Both perch and whitefish had an increase in range of δ15N. Perch did also have an increase in range of δ13C for the same time period while whitefish had a lower range of δ13C. The changes in fat content in wild fish and the changes in trophic niche that were found, indicate leakage of nutrients from the fish farm. In some areas this might have a positive effect on the production of wild fish whereas in other areas this could be a problem. Additionally, there is a need for further studies of the effect on wild fish in order for farmed fish to be a part of a sustainable food supply.